2022
DOI: 10.3390/ijerph19159420
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Associated Factors of Depression, Anxiety, and Stress among Healthcare Shift Workers during the COVID-19 Pandemic

Abstract: Background: The recent pandemic of COVID-19 has had a tremendous impact on healthcare frontliners. This study sought to assess healthcare shift workers’ depression, anxiety, and stress and its associated factors. Methods: The sampling frame includes healthcare shift workers directly managing COVID-19 cases around Klang Valley, Malaysia. The participants’ mental health status was assessed using the Depression, Anxiety, Stress Scale-21 (DASS-21). The associated factors specified in this study include sleep quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
6
1
Order By: Relevance
“…The findings of this study show that one in three HCWs reported having psychopathological levels of stress, anxiety, and depression, which is higher than that observed in other care settings [ 37 , 38 , 39 , 40 , 41 , 42 ]. This high prevalence should be considered a warning sign of possible negative psychosocial consequences from the acute phase of the pandemic, such as burnout or post-traumatic stress [ 15 , 43 ].…”
Section: Discussioncontrasting
confidence: 63%
“…The findings of this study show that one in three HCWs reported having psychopathological levels of stress, anxiety, and depression, which is higher than that observed in other care settings [ 37 , 38 , 39 , 40 , 41 , 42 ]. This high prevalence should be considered a warning sign of possible negative psychosocial consequences from the acute phase of the pandemic, such as burnout or post-traumatic stress [ 15 , 43 ].…”
Section: Discussioncontrasting
confidence: 63%
“…An earlier study in Malaysian HCWs also found that inactivity was strongly associated with increased odds of depression and anxiety during the COVID-19 period. 5 Particular attention is warranted regarding the programs promoting sports/exercises for HCWs in order to enhance their coping abilities for similar crises in the future. Another protective factor of depression and stress was the support with food/essential items by family.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been performed during the COVID-19 pandemic to show some potential influencing factors. For example, healthcare workers aged below 40 have been found to have a higher level of depressive and anxiety symptoms than those aged above 40 ( 6 , 15 ). Women have been found to be more vulnerable to the symptoms of depression ( 15 17 ) and anxiety ( 16 , 18 ) during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Women have been found to be more vulnerable to the symptoms of depression ( 15 17 ) and anxiety ( 16 , 18 ) during the COVID-19 pandemic. Nurses had a greater likelihood of developing depression than others, but any job type of healthcare worker developed anxiety at equal odds ( 6 ). And studies also revealed that healthcare workers with bachelor's degrees had significantly higher depression and anxiety than those with different education levels ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation